Development of methodology to test the electrical conductivity of Marandú grass seeds - Melo, Paulo Alexandre; Martins, Cibele; Alves, Edna; Vieira, Roberval (Revista Ciência Agronômica, 2018)
The electrical conductivity test enables the evaluation of seed vigor for a maximum period of 24 hours, but the need to count the seeds to obtain a sample for analysis makes it difficult to apply this test to small seeds, such as forage grasses. The objective of this study was to establish a practical methodology for testing the electrical conductivity of Brachiaria brizantha (Hochst. Ex A. Rich.) Stapf ‘Marandú’ seeds and to estimate its effect on seedling emergence in the field. The water content, germination, first germination count, first emergency count, percentage, and rate of seedling emergence speed in the laboratory, seedling emergence in the field, and electrical conductivity of eight batches of seeds was analyzed. In the last test, the periods of conditioning (2, 4, 6, 8, and 24 hours) and the volumes (50 and 75 mL) of distilled water used were evaluated and a new sampling methodology based on the seed volumes, obtained with the aid of a 1.5 ml plastic tube (Eppendorf), was developed. The experimental design was completely randomized, with four replications. The electrical conductivity test using volume sampling from seeds immersed in 75 mL of water and readings taken after 2 or 4 hours was the most efficient method for evaluating the vigor of marandú grass seed batches and provided information equivalent to seedling emergence in the field.